The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12958-021-00879-x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of extracellular vesicles secreted by primary human epithelial endometrial cells reveals key proteins related to embryo implantation

Abstract: Background Successful implantation is dependent on coordination between maternal endometrium and embryo, and the role of EVs in the required cross-talk cell-to-cell has been recently established. In this regard, it has been reported that EVs secreted by the maternal endometrium can be internalized by human trophoblastic cells transferring their contents and enhancing their adhesive and invasive capacity. This is the first study to comprehensively evaluate three EV isolation methods on human end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…Comparative proteome analysis of EP-sEVs ( versus E-sEVs) revealed molecular players of epithelial cell migration (BMPR2, DDR1, IGSF8, MST1R), embryo development (COPS3, CUL3, NOTCH1, PLCG1, ADAM10), cell-cell adhesion (SDCBP, EPCAM, NOTCH1), nitric oxide biosynthesis (e.g., DDAH2, AKT1 and SPR) and cell invasion (CSTB, DDR1, RAB25, ST14, TXN) ( Supplementary Figure S3 ; Supplementary Table S2 ). Importantly, EP-sEVs are enriched in key players shown to remodel endometrium to promote receptivity, or embryo to promote implantation processes ( Illera et al, 2000 ; Haslinger et al, 2013 ; Zhao et al, 2018 ; Segura-Benitez et al, 2022 ); enriched in regulators of endometrial receptivity (CTNNB1, EGFR, EPCAM, NOTCH1 and DDRI), as well as promote implantation processes (BMPR2, BTF3, COPS3, PLCG1, RAB14, ADAM10, CUL3, ITGAV and AKT1) ( Table 1 ). This further supports the successful hormonal priming of endometrial epithelial cells, the distinct molecular composition of sEVs, and highlights the pro-invasive function of EP-primed endometrial cell sEVs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative proteome analysis of EP-sEVs ( versus E-sEVs) revealed molecular players of epithelial cell migration (BMPR2, DDR1, IGSF8, MST1R), embryo development (COPS3, CUL3, NOTCH1, PLCG1, ADAM10), cell-cell adhesion (SDCBP, EPCAM, NOTCH1), nitric oxide biosynthesis (e.g., DDAH2, AKT1 and SPR) and cell invasion (CSTB, DDR1, RAB25, ST14, TXN) ( Supplementary Figure S3 ; Supplementary Table S2 ). Importantly, EP-sEVs are enriched in key players shown to remodel endometrium to promote receptivity, or embryo to promote implantation processes ( Illera et al, 2000 ; Haslinger et al, 2013 ; Zhao et al, 2018 ; Segura-Benitez et al, 2022 ); enriched in regulators of endometrial receptivity (CTNNB1, EGFR, EPCAM, NOTCH1 and DDRI), as well as promote implantation processes (BMPR2, BTF3, COPS3, PLCG1, RAB14, ADAM10, CUL3, ITGAV and AKT1) ( Table 1 ). This further supports the successful hormonal priming of endometrial epithelial cells, the distinct molecular composition of sEVs, and highlights the pro-invasive function of EP-primed endometrial cell sEVs.…”
Section: Resultsmentioning
confidence: 99%
“…While such components including ITGAV are enriched in EP-sEVs ( Table 1 ); suggests that sEVs may transfer integrins to modulate target cell surface expression ( Park et al, 2019 )—whether such targets (on sEVs or following their transfer to target cells) implicate trophectoderm cell interaction [e.g., ITGAV and B3 ( Altei et al, 2020 )], delivery/cell uptake ( Chen and Brigstock, 2016 ; Li et al, 2021 ) or tissue-specific homing ( Park et al, 2019 ) remain to be investigated. Moreover, ITGAV forms part of the integrin αVβ3 receptor expressed maternally and on embryo to mediate successful implantation ( Illera et al, 2000 ; Segura-Benitez et al, 2022 ). In addition to these invasion-associated surfaceome components, SERPINE1 is also expressed in extravillous trophoblasts (EVTs)—a highly invasive trophoblast lineage ( Bilban et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial reactivity and readiness for embryo implantation also result from the participation of exosomes in the communication process originating from endometrium and embryo [ 79 , 80 ]. One study reported that the presence of uterine fluid-derived exosomes during the preimplantation stage contains a higher abundance of proteins involved in cell apoptosis, while the uterine fluid-derived exosomes in the implantation stage had a higher abundance of proteins involved in cell adhesion [ 81 ]. Moreover, the highest number of exosomes are observed in the uterine fluid during the luteal phase of the menstrual cycle [ 82 , 83 ].…”
Section: The Role Of Exosomes In Embryo Implantationmentioning
confidence: 99%
“…Importantly, from women associated with a pregnancy outcome, transcripts were identified associated with implantation success (i.e., PMS2P5 , ANKRD18A , GLIS2‐AS1 , NPTN‐IT1 , and CERC7 ). Further, Rai and colleagues described that purified sEVs from UF of fertile women during the receptive phase were enriched in receptivity protein markers, including annexins (ANXA2/5/6), enzymes (DPP4, TGM2), and CAMs (ITGA1/2/6/B1, ICAM1) [173]. Such findings were further supported by a meta‐analysis of nine receptivity studies reporting 28 markers as co‐identified in sEVs from UF (including ANXA2/4, SPP1, DPP4, GPX3).…”
Section: Evs Regulate Embryo Implantationmentioning
confidence: 99%